2021
DOI: 10.2215/cjn.09280620
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Model for Real-Time Prediction of Intradialytic Hypotension

Abstract: Background and objectivesIntradialytic hypotension has high clinical significance. However, predicting it using conventional statistical models may be difficult because several factors have interactive and complex effects on the risk. Herein, we applied a deep learning model (recurrent neural network) to predict the risk of intradialytic hypotension using a timestamp-bearing dataset.Design, setting, participants, & measurementsWe obtained 261,647 hemodialysis sessions with 1,600,531 independent timestamps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…Moreover, real-time data at 1-min intervals were used to detect IDH events in this study. In some studies, time-varying variables were used to improve the efficacy of the prediction model, but real-time data continuously generated from the dialysis machine were not used, as in our study ( 8 ). Similarly, a previous study showed the feasibility of using data continuously measured by the hemodialysis machine to predict outcomes ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, real-time data at 1-min intervals were used to detect IDH events in this study. In some studies, time-varying variables were used to improve the efficacy of the prediction model, but real-time data continuously generated from the dialysis machine were not used, as in our study ( 8 ). Similarly, a previous study showed the feasibility of using data continuously measured by the hemodialysis machine to predict outcomes ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The large quantity of biosignals necessitates advanced or novel analytics that range from collection to interpretation [ 24 ]. Machine learning, including deep learning, is a rapidly developing branch of artificial intelligence that has shown promise for use in clinics [ 13 , 25 ]. A major limitation in utilizing biosignals for artificial intelligence-based clinical purposes is the lack of data storage [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring biosignals increases the awareness of their clinical importance because they can serve as indicators for unpredictable events during routine or urgent practice. Hemodialysis per se changes the biosignals of patients with or sometimes without symptoms, and thus monitoring changes in biosignals may allow for tracing or predicting hemodynamic complications during hemodialysis [ 11 13 ]. Some studies have traced intradialytic biosignals such as BP and ECG, and the risk of hemodynamic complications and relevant outcomes could be identified in detail by monitoring these signals [ 8 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have also used DL to investigate hemodialysis. Akl et al 14 suggested decades ago that the neural network can achieve artificial-intelligent dialysis control, and studies on intradialytic hypotension predictions [15][16][17][18] , the optimal dry weight setting 19 , and anemia control 20 for hemodialysis have been presented. DL in research has also expanded to other kidney diseases to predict acute kidney injury outcomes 21,22 and hyperkalemia 23 .…”
Section: Discussionmentioning
confidence: 99%